(untitled) (Jurnal Manajemen Pembangunan Daerah, 2025)
ABSTRACT This research analyzes the stock performance of PT Bank Syariah Indonesia Tbk (BSI) post-merger and compares it to the performance of Indonesia’s four largest banks (BCA, BRI, Mandiri, and BNI). The study applies both fundamental and technical analysis approaches. The findings indicate that BSI’s stock experienced a remarkable growth of +983.02% during 2020–2025, significantly outperforming the “Big Four” banks despite having a smaller market capitalization. Key drivers behind this growth include the merger, increasing positive sentiment toward the national sharia economy, improved financial performance, and digitalization strategies. Projections suggest that BSI could enter the top 10 companies on the Indonesia Stock Exchange in terms of market capitalization within the next five years, provided the current growth trend continues. This research contributes to a deeper understanding of the prospects of Islamic banking in Indonesia and serves as a reference for investors and policymakers. Keywords: BSI Stock, Fundamental Analysis, Merger, Sharia Banking, Technical Analysis.